1991
DOI: 10.1007/bf00687317
|View full text |Cite
|
Sign up to set email alerts
|

D-3-Deoxy-3-substitutedmyo-inositol analogues as inhibitors of cell growth

Abstract: A number of unnatural D-3-deoxy-3-substituted myo-inositols were synthesized and their effects on the growth of wild-type NIH 3T3 cells and oncogene-transformed NIH 3T3 cells were studied. The compounds were found to exhibit a diversity of growth-inhibitory activities and showed selectivity in inhibiting the growth of some transformed cells as compared with wild-type cells. Remarkably, D-3-deoxy-3-azido-myo-inositol exhibited potent growth-inhibitory effects toward v-sis-transformed NIH 3T3 cells but had littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

1992
1992
2005
2005

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 54 publications
0
23
0
1
Order By: Relevance
“…One class of drugs against Candida includes fluoro-nucleoside analogues such as 5-fluorocytosine (Georgopapadakou & Walsh, 1996). Moreover, fluorinated myo-inositol analogues such as 3-fluoro-3-deoxy-myoinositol have been reported to possess anti-proliferative activity in cancer cells through inhibition of phosphatidylinositol signalling (Powis et al, 1991;Offer et al, 1993;Johnson et al, 1993). Hence, our finding that 3-fluoro-3-deoxy-myo-inositol is recognized by the C. albicans myoinositol transporter with similar affinity as myo-inositol is particularly encouraging to further probe the Candida myo-inositol transporter as an attractive target for rational drug design and delivery of cytotoxic substrate analogues.…”
Section: Discussionmentioning
confidence: 99%
“…One class of drugs against Candida includes fluoro-nucleoside analogues such as 5-fluorocytosine (Georgopapadakou & Walsh, 1996). Moreover, fluorinated myo-inositol analogues such as 3-fluoro-3-deoxy-myoinositol have been reported to possess anti-proliferative activity in cancer cells through inhibition of phosphatidylinositol signalling (Powis et al, 1991;Offer et al, 1993;Johnson et al, 1993). Hence, our finding that 3-fluoro-3-deoxy-myo-inositol is recognized by the C. albicans myoinositol transporter with similar affinity as myo-inositol is particularly encouraging to further probe the Candida myo-inositol transporter as an attractive target for rational drug design and delivery of cytotoxic substrate analogues.…”
Section: Discussionmentioning
confidence: 99%
“…This mode of inhibition would prevent Akt translocation to the plasma membrane and activation [73]. The feasibility of this approach was suggested by the demonstration that D-3-deoxy-myo-inositols inhibited the growth of transformed cells [74]. It was subsequently found that the inositol derivative DPI (6) had an IC 50 of 35 µM against H-29 colon cancer growth [75].…”
Section: B Phosphatidylinositol Analog Inhibitorsmentioning
confidence: 97%
“…This mode of inhibition would prevent Akt translocation to the plasma membrane and activation. The feasibility of this approach was suggested by the demonstration that D-3-deoxy-myo-inositols inhibited the growth of transformed cells (Powis et al, 1991). It was subsequently found that the inositol derivative DPI had an IC 50 of 35 mM against H-29 colon cancer cell growth .…”
Section: Pi Analog Inhibitorsmentioning
confidence: 99%